Activation of the bacterial thermosensor DesK involves a serine zipper dimerization motif that is modulated by bilayer thickness - Cybulski, Larisa Estefania (2015)
DesK is a bacterial thermosensor protein involved in maintaining membrane fluidity in response to changes in environmental temperature. Most likely, the protein is activated by changes in membrane thickness, but the molecular mechanism of sensing and signaling is still poorly understood. Here we aimed to elucidate the mode of action of DesK by studying the so-called "minimal sensor DesK" (MS-DesK), in which sensing and signaling are captured in a single transmembrane segment. This simplified version of the sensor allows investigation of membrane thickness-dependent protein-lipid interactions simply by using synthetic peptides, corresponding to the membrane-spanning parts of functional and nonfunctional mutants of MS-DesK incorporated in lipid bilayers with varying thicknesses. The lipid-dependent behavior of the peptides was investigated by circular dichroism, tryptophan fluorescence, and molecular modeling. These experiments were complemented with in vivo functional studies on MS-DesK mutants. Based on the results, we constructed a model that suggests a new mechanism for sensing in which the protein is present as a dimer and responds to an increase in bilayer thickness by membrane incorporation of a C-terminal hydrophilic motif. This results in exposure of three serines on the same side of the transmembrane helices of MS-DesK, triggering a switching of the dimerization interface to allow the formation of a serine zipper. The final result is activation of the kinase state of MS-DesK.